Architecture Exploration and Validation of an Embedded System using a Model-Based Design Approach - Vikström, Peter (My University, 2007)
New technology and especially the technology development going on in the area of programmable integrated circuits supporting both soft- and hardcore processors and a variety of different IP blocks and interfaces enable many possible realisations of an embedded system platform. During the development of such an embedded system architecture there are many architectural design decisions and trade-offs that have to be taken affecting issues like performance, price, functionality, reliability and development time of the embedded system. To help the design architect in taking these decisions and trade-offs a design space exploration of three different embedded system processor environments are performed with respect to the presumed performance of the architectures. The evaluated systems include both a traditional processor-based solution and two FPGA-based System-on-Chip (SoC) solutions. The performance numbers are obtained by simulating a model representing the application that is mapped to models of the embedded system architectures. The results of the simulations show that there are differences in terms of performance for the evaluated embedded system architectures. Further the strengths and weaknesses of the architectures are identified, which is valuable information not only when doing hardware architectural design decisions and trade-offs, but also when optimizing the software and application to run efficiently on the hardware architecture.
Keywords: Embedded System Architecture; Performance Evaluation; Design Space Exploration; Simulation; fi=Automaatiotekniikka|en=Automation Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|